The Influence of Organizational Culture Through Intervening Variables of Organizational Behavior on the Performance of the Yogyakarta Cooperative and SME Service Case Study - Arliza Putri (Universitas 17 Agustus 1945 Semarang, 2023)
Abstract. Organizational culture is very important for the progress of an organization or company. A good organizational culture is expected to be able to influence employee performance and organizational behavior. Maximum performance is also expected to have an impact on organizational behavior. This research was carried out at the Yogyakarta Cooperatives and SMEs Service. This research aims to find out whether the organizational culture in the Yogyakarta Cooperatives and SMEs Service has an influence on organizational performance and behavior. The research method used is quantitative, where data is collected through questionnaires with the sampling method used is saturated sampling, the sample used is all employees in the Yogyakarta Cooperatives and UKM Service, totaling 40 people. Apart from using a questionnaire, researchers also conducted interviews to gain more information about the Yogyakarta Cooperatives and SMEs Department. The data analysis used is path analysis. The results of this research provide the conclusion that the organizational culture used by the Yogyakarta Cooperatives and UKM Service is the